Pengaruh Karakteristik Individu terhadap Kelelahan Pekerja Pengolahan Gudeg CV. X Yogyakarta - Ardinendradewi, Qonitya; Setyaningsih, Yuliani; Kurniawan, Bina (Jurnal Riset Kesehatan Masyarakat, 2022)
The informal sector is currently experiencing a more rapid growth process than the formal sector so that it becomes one of the pillars of the Indonesian economy. One of the industries engaged in the informal sector is gudeg processing. Processing gudeg is a workplace that has a hot climate that comes from the furnace to cook gudeg. In addition, other influencing factors are individual factors in the form of age, increasing age can cause workers to become easily tired. In addition to age, the working period of workers varies, some have been in work for a long time or not. The purpose of this research is to analyze the effect of individual characteristics on fatigue of gudeg processing workers. This research was conducted through quantitative research, the method used was cross sectional research which was used to determine the effect of the independent variable and the dependent variable. Data collection was carried out using a Reaction timer, Subjective Self Rating Test (SSRT) from the Processing Fatigue Research Committee (IFRC) and sheet respondent's questionnaire. The statistical test used was univariate test and bivariate chi-square test. The results showed that there was no influence between age, gender, and years of service on work fatigue.